Intervensi Partisipatif melalui Pemasangan Palang Jejak Alam untuk Penguatan Identitas Visual Desa Wisata Tompo Bulu, Pangkep - Zainal Abidin Achmad; Rossyda Priyadarshini; Muchlisniyati Safeyah; Wahyu Mustiko Sejati (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
Village tourism is increasingly viewed as strategic because it not only drives economic growth but also preserves culture and the environment. Tompo Bulu Village in Pangkep Regency has natural tourism potential in the form of hills, trekking trails, waterfalls, and caves, but the lack of navigation infrastructure makes it difficult for tourists. Through the 2025 National Community Service Program (KKN Kebangsaan XIII), participatory community service was conducted, involving students and local residents in installing nature trail markers. The implementation method included field observation, village deliberations, design, construction, and installation of signs, as well as evaluation through route trials. Additionally, pre- and post-tests were conducted to gauge community understanding of the importance of tourism navigation and sustainable destination management. The results of the activity resulted in the installation of 11 identity boards and directions at strategic points leading to Mount Batu Pute, Tombolo Waterfall, and Goa Passosoang Tunabbaka. The impact was seen in increased tourist accessibility, strengthened visual identity of the destination, digital promotion through social media, and the growth of local micro-business opportunities. Theoretical analysis shows that this simple intervention supports the principles of Community-Based Tourism, strengthens the destination's image, and paves the way for sustainable ecotourism. This activity faced limitations of time, funding, and material durability, yet it succeeded in making a real contribution to the transformation of Tompo Bulu into a tourist village.